2018
DOI: 10.1038/s41598-018-35608-9
|View full text |Cite
|
Sign up to set email alerts
|

Nanotube-structured Na2V3O7 as a Cathode Material for Sodium-Ion Batteries with High-rate and Stable Cycle Performances

Abstract: Sodium ion batteries meet the demand for large-scale energy storage, such as in electric vehicles, due to the material abundance of sodium. In this report, nanotube-type Na2V3O7 is proposed as a cathode material because of its fast sodium diffusivity, an important requirement for sodium ion batteries, through the investigation of ~4300 candidates via a high-throughput computation. High-rate performance was confirmed, showing ~65% capacity retention at a current density of 10C at room temperature, despite the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 22 publications
(42 reference statements)
1
18
0
Order By: Relevance
“…Therefore, the high-throughput computational exploration partly succeeded in screening the Mg 2+ conductive oxides, though the evaluated migration energies obtained by BVFF calculations deviated significantly from those obtained by DFT-MD studies and experimental observations for Mg 0.6 Al 1.2 Si 1.8 O 6 . We infer that the present BVFF calculations may systematically overestimate the migration energy, as our previous study for Li ion conductors confirmed systematic overestimation compared to DFT-derived migration energies [23]. The trend of conduction values may be captured even for Mg-O systems, and quantitative improvement is required for the present high-throughput scheme.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Therefore, the high-throughput computational exploration partly succeeded in screening the Mg 2+ conductive oxides, though the evaluated migration energies obtained by BVFF calculations deviated significantly from those obtained by DFT-MD studies and experimental observations for Mg 0.6 Al 1.2 Si 1.8 O 6 . We infer that the present BVFF calculations may systematically overestimate the migration energy, as our previous study for Li ion conductors confirmed systematic overestimation compared to DFT-derived migration energies [23]. The trend of conduction values may be captured even for Mg-O systems, and quantitative improvement is required for the present high-throughput scheme.…”
Section: Discussionsupporting
confidence: 45%
“…In this respect, we recently performed a high-throughput exhaustive search for fast ion conductors via automated material simulations, using the force field technique and percolation theory [22]. We demonstrated the effectiveness of novel high-rate electrodes comprising Na 2 V 3 O 7 as cathodes for Na-ion batteries [23].…”
Section: Introductionmentioning
confidence: 99%
“…[74][75][76] Nevertheless, sodium cations have several advantages over lithium ones, and development is currently being intensively carried out to switch to sodium-ion polymer batteries. [77][78][79][80] The conductivities of lithium and sodium are comparable to a first approximation, 81 and this allows some comparisons. The ionic conductivity of the best solid polymer electrolytes based on blends of lithium salts with poly(p-phenylene) with attached flexible oligo(ethylene oxide) sidechains is about 10 -4.5 -10 −6 S cm -1 .…”
Section: Film Propertiesmentioning
confidence: 95%
“…Na 2 V 3 O 7 was synthesized as reported in previous works. 31,32 The Na 2 V 3 O 7 electrode sheet was prepared by pasting a slurry made of Na 2 V 3 O 7 (80 wt%) mixed with Ketjen black (10 wt%, KB, Lion Corp.) and polyvinylidene fluoride (10 wt%, PVdF, Kureha) in N-methylpyrrolidone (NMP, Wako) onto Al foil using a 100 µm doctor blade and then dried at 60°C. The dried electrode sheets were punched into 12 mm diameter pieces and further dried overnight at 150°C (for hard carbon) or 120°C (for Na 2 V 3 O 7 ) in a vacuum.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%